Novel 1-benzyl-2-indolinone indole hybrids as tyrosine kinase inhibitors: Design, synthesis, and biological activity evaluation - Cihan-Ustundag, Gokce; Cinek, Tugce; Sancar, Serap; Yildirim, Merve; Genc-Akar, Oykum; Ozen-Eroglu, Gunes; Karali, Nilgun (Elsevier France-Editions Scientifiques Medicales Elsevier, 2026)
In the present study, new 1-benzyl-2-indolinone indole hybrids (4a-s) were synthesized and their cytotoxic effects were determined against human breast (MCF-7 and MDA-MB 231), lung (A549), kidney (CAKI-1 and A498), colon (HT-29 and HCT-116), and pancreas (MIA PaCa-2) cancer cells by MTT assay. Some of the tested compounds showed significantly better inhibitory effects and safety profiles than sunitinib malate against A498 and MIA PaCa-2 cells. Compound 4s showed a selective and significant cytotoxic effect on MIA PaCa-2 cells (IC50 = 0.15 mu M; SI > 666.7). Compound 4b displayed significant cytotoxic effects on both A498 (IC50 = 0.87 mu M; SI > 58.3) and MIA PaCa-2 (IC50 = 0.13 mu M; SI = 390.0) cells. Compound 4b in A498 cells and compounds 4a-c, 4h, and 4s in MIA PaCa-2 cells significantly decreased general tyrosine kinase activity and induced apoptosis, accompanied by reduced ERK signalings. The inhibitory activities of compounds 4a-c, 4h, and 4s against SRC, PDGFR-beta, and c-MET kinases were assessed in MIA PaCa-2 cells. Compounds 4a, 4b, 4h, and 4s inhibited PDGFR-beta, with 4h and 4s additionally targeting c-MET, while 4a, 4b, and 4h also demonstrated SRC inhibition. In this study, lead compounds 4b and 4s were identified as selective cytotoxic agents against human pancreatic carcinoma cells through induction of apoptosis and inhibition of SRC/PDGFR-beta/c-MET signaling. Notably, compounds 4b and 4s demonstrated a significantly better safety profile than sunitinib malate against noncancerous cells, underscoring their broader therapeutic potential. To understand their potential binding modes, molecular modeling studies were performed at the ATP-binding domains of SRC, PDGFR, and c-MET kinases.
Keywords: 2-Indolinone; Indole; Cytotoxicity; Tyrosine kinase; SRC; PDGFR; c-MET; Apoptosis; AKT/ERK